FEATURES OF CLINICAL AND DIAGNOSTIC CRITERIA OF MYCOPLASMA PNEUMONIA IN CHILDREN (International Journal of Scientific Pediatrics, 2023)
Annotation. Despite scientific research, due to the complexity of early diagnosis of the etiological factor, the peculiarities of clinical and laboratory manifestations of the disease, the problem of atypical pneumonia in children remains unresolved. Timely detection of the etiological factor of atypical pneumonia largely determines the effectiveness of antibiotic therapy, which dramatically affects the course and outcome of the disease, and cultural diagnosis is difficult, since mycoplasma is an intracellular pathogen and is not detected even with smear microscopy. One of the current directions in the study of the pathogenesis of various inflammatory diseases is to determine the status of pro-inflammatory and anti-inflammatory cytokines, which are sensitive and specific biomarkers of the body's response to infection. Variants of cytokine profile indicators in pediatric practice and their relationship with the course of pneumonia in children are only indicative. The purpose of the study was to study the clinical diagnostic criteria for mycoplasmal pneumonia in children.Materials and research methods. We examined 60 patients who, depending on the etiological factor of the disease, patients with community-acquired pneumonia were divided into 2 groups: group I - 30 patients with mycoplasmal etiology, group II - 30 patients with pneumonia of typical etiology. The results of the studies showed that immunological disorders in sick children with mycoplasmal pneumonia are characterized by a significant increase in pro-inflammatory and anti-inflammatory cytokines compared with standard values.
Keywords: diagnostics; clinic; atypical pneumonia; children